Role of Complement and Histones in Sepsis - Zetoune, Firas S.; Ward, Peter A. (Frontiers in Medicine, 2020)
The wide use of the mouse model of polymicrobial sepsis has provided important evidence for events occurring in infectious sepsis involving septic mice and septic humans. Nearly 100 clinical trials in humans with sepsis have been completed, yet there is no FDA-approved. Our studies of polymicrobial sepsis have highlighted the role of complement activation products (especially C5a anaphylatoxin and its receptors C5aR1 and C5aR2) in adverse effects of sepsis. During sepsis, the appearance of these complement products is followed by appearance of extracellular histones in plasma, which have powerful proinflammatory and prothrombotic activities that cause cell injury and multiorgan dysfunction in septic mice. Similar responses occur in septic humans. Histone appearance in plasma is related to complement activation and appearance of C5a and its interaction with its receptors. Development of the cardiomyopathy of sepsis also depends on C5a, C5a receptors and histones. Neutralization of C5a with antibody or absence of C5aR1 blocks appearance of extracellular histones and cell and organ failure in sepsis. Survival rates in septic mice are greatly improved after blockade of C5a with antibody. We also review the various strategies in sepsis that greatly reduce the development of life-threatening events of sepsis.